Mesenchymal stem cell-based therapy for osteoarthritis: a systematic review and meta-analysis of clinical outcomes and functional recovery - Wang, Jincheng; Xue, Hao; Shi, Mingfei; Chen, Renshou (Frontiers in Cell and Developmental Biology, 2026)
BackgroundsThis study aimed to evaluate the efficacy and safety of mesenchymal stem cell (MSC) therapy for osteoarthritis (OA) through a systematic review and meta-analysis of randomized controlled trials (RCTs), focusing on patient-reported pain and functional outcomes.MethodsA comprehensive literature search was conducted across multiple databases including PubMed, Embase, Web of Science, and Cochrane Library from inception to 1st October 2025. RCTs comparing intra-articular MSC injections with control interventions (placebo, hyaluronic acid, or other active treatments) in adult OA patients were included. Primary outcomes were changes in pain intensity measured by Visual Analog Scale (VAS) and functional improvement assessed by International Knee Documentation Committee (IKDC) score. Secondary outcomes included Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Lequesne index, Lysholm score, and Tegner activity scale. Data were pooled using random-effects models and expressed as mean differences (MD) with 95% confidence intervals (CI).ResultsEleven RCTs involving 811 patients were included. MSC therapy demonstrated significant reduction in VAS pain scores compared to controls (MD -4.08, 95% CI -5.56 to −2.61, p < 0.00001), with the most pronounced effects at 24-month follow-up (MD -3.31, 95% CI -5.18 to −1.44, p = 0.0005). Significant improvements were observed in IKDC scores (MD 2.88, 95% CI 0.28 to 5.47, p = 0.03), WOMAC index (MD -11.05, 95% CI -15.97 to −6.14, p < 0.0001), Lequesne index (MD -5.32, 95% CI -5.91 to −4.74, p < 0.00001), Lysholm score (MD 5.07, 95% CI 1.86 to 8.29, p = 0.002), and Tegner activity scale (MD 0.44, 95% CI 0.25 to 0.62, p < 0.00001). The therapeutic effects showed a time-dependent pattern, with maximal benefits observed at 24-month follow-up across all outcome measures.ConclusionIntra-articular MSC injection is an effective treatment for osteoarthritis, providing significant and durable improvements in pain relief, functional recovery, and activity levels up to 24 months post-treatment. The time-dependent nature of clinical benefits suggests a potential disease-modifying mechanism of action. MSC therapy represents a promising regenerative approach for OA management that warrants further investigation in large-scale trials.